Upaya Pencegahan Resiko Stroke Pada Lansia Melalui Pendidikan Kesehatan Di Panti Werdha Surya Jemursari Surabaya - Ermalynda Sukmawati; Agustina Chriswinda Bura Mare; Steven Aldo Marcello (LPMP Imperium, 2024)
Strokes are experienced by many elderly people and affect health status, resulting in impaired mobility and paralysis. To reduce the incidence of stroke in the elderly, health education and regular blood pressure checks are provided. The aim of community services at the Jemursari Nursing Home is to prevent the risk of stroke that occurs in the elderly. The method of implementing community services at the Surya Nursing Home is through education about stroke. Next, the team measured blood pressure, uric acid and blood sugar on 56 of the 71 elderly people living at the Surya Nursing Home. Examination results from 56 elderly people, blood pressure: elderly people who had blood pressure >140/90 were 19 female participants and 7 male participants. Abnormal uric acid: 41 female participants and 8 male participants. Abnormal blood sugar was found in 7 female participants and 1 male participant. The output of this community service activity is to publish in the form of scientific articles for community service members which can increase knowledge, insight into how to prevent and carry out regular checks on blood pressure and other tests related to stroke.